Challenges and Benefits of ICT in Teaching and Learning English - Hamliyah Hamliyah; Dewi Untari; Lutfiah Lutfiah; Siti Yuliana; Setyorini Dwi Agustini (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
In Digital Era, E-learning involves the use of the internet and mobile learning, including all types of gadgets. English teachers are required to apply creative and innovative teaching models in designing ICT-based learning that is appropriate to the needs of students. This study is to identify the types of ICT tools and describes the challenges and benefits of ICT in English Language Teaching and Learning at SMKN 8 Jember. It employs a descriptive qualitative method with interviews and documentation of lesson plans for data collection. The participants include 100 students from X, XI, and XII grades, and the English teachers. Data analysis was conducted through data reduction, data display, and drawing conclusions. The findings indicate the types of ICT media used by teachers in the teaching and learning and the implementation of ICT as a media and learning resource with the students’ responses about 57% strongly agree and 43% agree. It means that teachers already applied the ICT in classroom quite good because they have effectively utilized ICT in English language teaching easier for students to grasp the learning materials, learning motivation, and learning outcomes. Besides the benefits, it is hope to effectively address the challenges of ICT use in learning English, teachers can receive targeted training and support in several areas. These programs aim to build their confidence, technical skills, and pedagogical strategies for integrating ICT into their teaching practice.